Basic psychological needs satisfaction, need frustration and entrepreneurial intention - Hassan, Arif (2015)
The present study proposed to investigate whether satisfaction and frustration for autonomy, competence and relatedness identified as three universal Basic Psychological Needs within Self-Determination Theory of motivation (Ryan and Deci, 2000) contribute differently to entrepreneurial intention of undergraduate students (N =438) in Malaysia. Structural equation modelling was used to test the hypothesized model and structural relationships. The findings demonstrated that students’ willingness to engage in starting their own businesses can be influenced by both need satisfaction and frustration. This implies that students may act volitionally and choose to be entrepreneurs and/or they may engage in entrepreneurial behaviour either out of obligation or necessity, although being volitional seems to be a stronger and dominant predictor of entrepreneurial intention.